Risks management in the hospital environment: incidence and risk factors associated with falls and pressure injuries in a clinical unit - Rayane Oliveira Cedraz; Cristiane Helena Gallasch; Eugenio Fuentes Pérez Júnior; Helena Ferraz Gomes; Ronilson Gonçalves Rocha; Vivian Aline Mininel (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To evaluate the incidence and risk factors associated with falls and pressure injuries in a clinical unit. Methods: A quantitative, cross-sectional, descriptive-exploratory study was conducted at a university hospital in Rio de Janeiro using secondary data from patient records and information of registers of patients treated in 2015/2016. Data were analyzed using descriptive and inferential statistics. Results: Of the 157 treated patients, women, cardiovascular (43.9%) and oncological diseases (35.0%) predominated. The risk and incidences of falls and pressure injuries were higher in men. There were significant associations of gender with the risk of falling, the occurrence of falls and pressure injuries, and between the length of hospital stay and risk of falling. Conclusion: Risk management is essential to promote patient safety and improve quality of health care. Nurse staff plays a fundamental role in the process of guiding activities, updating the nursing team and evaluating interventions. The use of tools, such as protocols and indicators, allows the optimization of the work process and the achievement of these goals.